'A band of public‐spirited women': middle‐class female philanthropy and citizenship in Bolton, Lancashire before 1918. Issue 2 (15th March 2016) - Moore, Francesca
Abstract : In the 19th and early 20th centuries, despite the cultural ideal of private and public as separate spheres and a lack of formal voting rights, many middle‐class women engaged in philanthropic and social work outside the home. Taking as its focus a group of middle‐class women in Bolton, Lancashire, this paper conducts a prosopography, or group biography, in order to shed light on female citizenship and make a historical contribution to literature on citizenship beyond voting rights. The paper uses archive traces to reconstruct the experience of the female philanthropist and understand her motivations. The focus of the paper is a new theoretical approach to women's citizenship in the early 20th century. Using Michel Foucault's concept of biopolitics, or life politics, the paper reconceptualises women's social work as a form of biopolitical patriotism that was the basis of a scalar claim to citizenship. This historical evidence from Bolton reveals that biopolitical action was not solely the preserve of the state. Women claimed fitness for citizenship and the vote by nation‐building, carrying out work that shaped children into the citizens of the future and safeguarded the moral and physical health of the nation.